Identification of AIM2 as a downstream target of JAK2V617F. Issue 1 (December 2015) - Liew, Ei; Araki, Marito; Hironaka, Yumi; Mori, Seiichi; Tan, Tuan; Morishita, Soji; Edahiro, Yoko; Ohsaka, Akimichi; Komatsu, Norio
Abstract Background The gain-of-function mutation JAK2V617F is frequently found in Philadelphia-chromosome-negative myeloproliferative neoplasm (MPN) patients. However, the tumorigenic properties of JAK2V617F have mostly been characterized in in vivo and in vitro murine models due to the lack of appropriate human cell lines. Methods Using the multipotent hematologic cell line UT-7/GM, we established D9, a novel human cell line that expresses JAK2V617F upon tetracycline addition. We assessed cellular differentiation in UT-7/GM cells when JAK2V617F was induced, and we used microarrays to analyze changes in mRNA expression caused by JAK2V617F. Results Using the human D9 cell line, we demonstrated that the induction of JAK2V617F leads to cytokine-independent cell growth with increased STAT activation and erythroid differentiation, mimicking the characteristics observed in polycythemia vera, making it a suitable in vitro model for studying this disorder. Interestingly, JAK2V617F-dependent erythroid cell differentiation was blocked when GM-CSF was added to the culture, suggesting that the GM-CSF pathway antagonizes JAK2V617F-induced erythroid cell differentiation. Our microarray analysis identified several genes involved in inflammasome activation, such as AIM2, IL1B, and CASP1, which were significantly up-regulated in JAK2V617F-induced cells. Conclusions The observed inflammasome activation following JAK2V617F induction is consistent with a recent report demonstrating the involvement of IL1B in myelofibrosis development in a JAK2V617F model mouse. These results indicate that the D9 cell line should be useful for characterizing the signaling pathways downstream of JAK2V617F, allowing for the identification of effector molecules that contribute to the development of MPN.